Getting clear about equivocal concepts: critical review of Millikan's 'On clear and confused ideas' - Shea, N (Philosophy Centre of the University of Lisbon, 2002)
Just how far can externalism go? In this exciting new book Ruth Millikan explores a radically externalist treatment of empirical concepts. For the last thirty years philosophy of mind’s ties to meaning internalism have been loosened. The theory of content has swung uncomfortably on its moorings in a fickle current, straining against opposing ties to mind and world. In this book Millikan casts conceptual content adrift from the thinker: what determines the content of a concept is not cognitively accessible. She has only the stanchion of the world to hold her theory fast. She hopes that the tide will turn, and the theory of meaning will come stably to rest downstream of this anchor. This book is a bold exploration of how that might be achieved.